Influence of nanoscale structuralisation on the catalytic performance of ZIF-8: a cautionary surface catalysis study. Issue 34 (1st August 2018) - Linder-Patton, Oliver M.; de Prinse, Thomas J.; Furukawa, Shuhei; Bell, Stephen G.; Sumida, Kenji; Doonan, Christian J.; Sumby, Christopher J.
Abstract : Nanoscale structuralisation is demonstrated to influence the stability and catalytic properties of zeolitic imidazolate framework-8. Abstract : Although metal–organic frameworks (MOFs) have been shown to catalyse a wide range of reactions, understanding the influence of nanoscale structuralisation ( e.g. crystal size and morphology) on their performance is a difficult challenge. Here, we have prepared Zn(2-mIM)2 (ZIF-8; 2-mIM − = 2-methylimidazolate) crystals of varied size and morphology, and studied the catalytic properties of these samples in the context of the transesterification of vinyl acetate with hexanol. ZIF-8 has previously been shown to catalyse reactions at Lewis acidic sites at the crystal surface and at defect sites. The substrates were selected as they are significantly larger than the pore apertures, allowing the reaction to be confined to the surface of the crystals and providing the best opportunity to understand the influence of the structuralisation on the observed properties. In this case, the rate of hexyl acetate production increased as the crystal size was reduced; however, the effect of crystal morphology on the rate of reaction was not appreciable due to the instability of ZIF-8 under catalytic conditions. It was clearly observed that the surface of ZIF-8 was unstable in catalytic conditions featuring hydrophobic reagents with a polar functional groups, with scanning electron microscopy (SEM) revealing indiscriminate etching of all crystal surfaces. Atomic adsorption spectrometry (AAS) analyses confirmed the etching led to significant leaching of Zn 2+, which was observed to contribute considerably to the catalytic activity of ZIF-8. Our results highlight the need for fundamental characterisation of MOF catalysts to enable their deployment under a wider variety of catalytic conditions.